2018
DOI: 10.1080/01658107.2018.1454479
|View full text |Cite
|
Sign up to set email alerts
|

Vision Loss from Choroidal and Pituitary Metastases Secondary to Renal Cell Carcinoma: A Case Report

Abstract: A 62-year-old male with a history of metastatic clear cell renal cell carcinoma (ccRCC) presented with decreased vision to 20/50 in the left eye. Fundus examination revealed an elevated, amelanotic mass lesion in the superotemporal macula, without involvement of the central macula by subretinal fluid or tumour. Given incongruity between the fundus findings and the degree of visual impairment, visual field testing was obtained, revealing a bitemporal hemianopia. Magnetic resonance imaging demonstrated optic chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Therefore, diagnosis of RCC should be suspected in patients presenting with a mass in the eyelid with a previous history of RCC, even if the patient presumes to be in remission. This was seen with the patient presented in this case and in another case where the patient was in remission of RCC for 20 years [3,4]. It has been reported that RCC metastasis to the eye can be the first presenting sign of RCC leading to a diagnosis of RCC in patients [1,2].…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Therefore, diagnosis of RCC should be suspected in patients presenting with a mass in the eyelid with a previous history of RCC, even if the patient presumes to be in remission. This was seen with the patient presented in this case and in another case where the patient was in remission of RCC for 20 years [3,4]. It has been reported that RCC metastasis to the eye can be the first presenting sign of RCC leading to a diagnosis of RCC in patients [1,2].…”
Section: Discussionsupporting
confidence: 69%
“…One study showed that only 3-7% of such masses were from the metastasis of tumors, with the majority of such tumors could be attributed to tumor metastases from the breast in women and lung and prostate in men [ 2 ]. The most common presenting ocular symptoms of ophthalmic tumors are proptosis or diplopia followed by ptosis, enophthalmos, pain, and decreased visual acuity [ 2 , 3 ]. RCC is a rare systemic malignancy comprising 2-4% of all tumors [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations